(untitled) (Eurasian Medical Research Periodical, 2024)
Lower urinary tract symptoms secondary to benign prostatic hyperplasia (prostate adenoma) are more common in older men and have a greater than 50% chance of developing the disease in men over 60 years of age[1]. Transurethral resection of the prostate (Turp), defined as the "gold standard" of surgical treatment of prostate adenoma recommended by the American Urological Association (AUA), is minimally invasive[2]. Insertion of a three-sided catheter after transurethral resection was standard practice to prevent bleeding caused by emptying the bladder. Urologists usually remove the catheter, allowing patients to attempt to urinate on their own. [5] the urethra is the second most important factor after traumatic urethral injury due to an increase in the number of transurethral interventions and catheterization and is a leading factor in the development of urethral structures